Pembelajaran Bahasa Arab Berbasis Common European Framework Of Reference For Language (CEFR) Di Indonesia - Talqis Nurdianto; Noor Azizi bin Ismail (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2020)
Learning and teaching Arabic for non-Arabic speakers continues to develop, from methods, teaching aid to curriculum. The development of learning and teaching follows the changing demands of the era and era of learners (students). This renewal of methods and media does not mean that the older version is forgotten altogether, but rather they became a platform to be improved thus giving a good impression on Arabic learners that learning Arabic is easy and fun. For Indonesians, Arabic, like any other foreign languages, is not their native language. Depending on the learners, learning Arabic has different levels of difficulty. The difficulty of learning is not always due to the language but also the student. The Common European Framework of Reference for Language (CEFR) in learning foreign languages in Europe is an alternative method chosen in learning English for non-English speakers in Europe. Can this theory be applied in Arabic learning, as can 40 foreign languages besides English? This study seeks to determine the effectiveness, opportunities and challenges of learning Arabic in Indonesia using CEFR by using descriptive qualitative methods. The level of formal education that refers to the age of students is not used in learning Arabic with CEFR. The CEFR theory in learning Arabic refers to Arabic language ability at each level and has the total of six levels.. A1 and A2 are for beginners, B1 and B2 for intermediate, and C1 and C2 for advanced levels. Arabic learning material arranged according to the competencies of each level makes it possible for anyone to learn it and occupy the level according to their abilities. Meanwhile, the implementation of CEFR in learning Arabic in Indonesia and its opportunities and challenges is still difficult to find, both in formal and non-formal education without support from the government. Keywords: CEFR, Arabic learning.